2015
DOI: 10.2169/internalmedicine.54.2956
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Origin of the Left Circumflex Artery from the Right Sinus of Valsalva: Non-ST-segment Elevation Myocardial Infarction

Abstract: An anomalous origin of the left coronary artery from the right sinus of Valsalva (RSV) is rare. We herein report the case of an 80-year-old woman who presented to the emergency department with chest pain. Emergent coronary angiography was performed following a diagnosis of non-ST segment elevation myocardial infarction. A right coronary angiogram showed that the common trunk originating from the RSV branched into the left anterior descending and right coronary arteries. Although the initial angiogram failed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In their anatomical study by Reig and Petit, the longest left main trunk was reported to be 23 mm and the average length was 10.8 ± 5.5 mm [ 5 ]. LMCA originating from the right sinus of valsalva (RSV) is extremely rare, and it is incidentally found in approximately 0.017% of all coronary artery angiographies [ 6 ]. Left coronary artery originating from the right sinus of valsalva may have 4 courses: between the aortic root and the pulmonary artery (interarterial course), transseptal course (subpulmonic course), anterior course originating from the right ventricle (anterior or prepulmonic course), and posterior course regarding the aortic root (retroaortic course).…”
Section: Discussionmentioning
confidence: 99%
“…In their anatomical study by Reig and Petit, the longest left main trunk was reported to be 23 mm and the average length was 10.8 ± 5.5 mm [ 5 ]. LMCA originating from the right sinus of valsalva (RSV) is extremely rare, and it is incidentally found in approximately 0.017% of all coronary artery angiographies [ 6 ]. Left coronary artery originating from the right sinus of valsalva may have 4 courses: between the aortic root and the pulmonary artery (interarterial course), transseptal course (subpulmonic course), anterior course originating from the right ventricle (anterior or prepulmonic course), and posterior course regarding the aortic root (retroaortic course).…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery anomalies are very rare, and are seen in less than 1% of the general population [ 4 ]. Particularly, LMCA originating from the right sinus of Valsalva (RSV) is extremely rare, and it is incidentally found in approximately 0,017% of all coronary artery angiographies [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first one is that exercise induced pressure between the pulmonary trunk and the aorta may lead to decreased coronary blood flow [ 8 ]. The second implies that, acute takeoff or hiatus like orifice in these arteries may lead to ischemia resulting in angina, syncope, congestive heart failure, arrhytmia and/or sudden death [ 5 ]. The third, being myocardial remodelling is related to poor prognosis due regional ischemic inflammatory histopathological changes [10].…”
Section: Discussionmentioning
confidence: 99%
“…6 have been proposed [3]. Anomalous left coronary artery originating from the right sinus of Valsalva may have four pathways: interatrial, trans-septal (or subpulmonic), anterior (or prepulmonic) and posterior to the aortic root (or retroaortic) [4]. A "high take-off" is variably referred to as the coronary origin above the sinotubular junction.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the setting of ACS, it may not be feasible. There are few reports on PCI in AOCCA of ACS-patients [3,4,7] and apart from one series of 5 culprit AOCCA's in ACS-patients [8], there is no systematic study of patients who underwent PCI of AOCCA, especially in emergency cases.…”
Section: Introductionmentioning
confidence: 99%